Understanding Motivations and Barriers of Female Start-up Founders in Czechia - Lomakina, Anastasia (2023)
This thesis addresses the existing research gap regarding female start-up founders in Czechia. The paper uses qualitative analysis to investigate the motivation and self-perceived barriers of active female founders in Czechia. To answer the outlined research questions, semi-structured in-depth interviews were conducted with 11 female start-up founders, and data were further analyzed via coding. The study found that female founders in Czechia are primarily motivated by entrepreneurial drive, past experience, and the pursuit of rewards. The findings on self-perceived barriers include societal and cultural barriers, structural and institutional barriers, and psychological barriers. The last chapter, moreover, provides a summary of the founders’ recommendations on how to overcome some of the identified obstacles. The study concludes with theoretical and practical contributions for Czech governmental bodies and aspiring female founders, as well as outline the limitations and implication for future research.